2021
DOI: 10.3390/ph14020149
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNA-7 in the Biology of Cancer and Modulation of Drug Resistance

Abstract: MicroRNAs (miRNAs, miRs) are small non-coding RNA (ncRNA) molecules capable of regulating post-transcriptional gene expression. Imbalances in the miRNA network have been associated with the development of many pathological conditions and diseases, including cancer. Recently, miRNAs have also been linked to the phenomenon of multidrug resistance (MDR). MiR-7 is one of the extensively studied miRNAs and its role in cancer progression and MDR modulation has been highlighted. MiR-7 is engaged in multiple cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 165 publications
0
11
0
Order By: Relevance
“…MiR-7-5p connects different signaling pathways through feedback and feedforward loops and is involved in differentiation, regulation of proliferation, apoptosis, migration, chromatin remodeling, and multidrug resistance. [ 53 , 54 ] MiR-7 acts mainly as a tumor suppressor in various cancer types [ 53 ] ; however, evidence suggests that it may also act as an oncogene in lung cancer. [ 55 ] Elevated miR-7 expression levels in lung tumors compared to normal tissues and metastases have been found in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-7-5p connects different signaling pathways through feedback and feedforward loops and is involved in differentiation, regulation of proliferation, apoptosis, migration, chromatin remodeling, and multidrug resistance. [ 53 , 54 ] MiR-7 acts mainly as a tumor suppressor in various cancer types [ 53 ] ; however, evidence suggests that it may also act as an oncogene in lung cancer. [ 55 ] Elevated miR-7 expression levels in lung tumors compared to normal tissues and metastases have been found in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is crucial to further explore whether TRMT112 promotes tumorigenesis and development by interacting with SART1. As oncogenes or tumor suppressor genes [ 42 , 43 ], noncoding RNAs, such as lncRNA, miRNA, and tRNA, participate in the regulation of cell proliferation [ 44 , 45 ], apoptosis [ 46 ], metastasis [ 47 , 48 ], differentiation [ 49 ], and other biological processes. GO enrichment and KEGG analyses illustrated that TRMT112 might be implicated in tumorigenesis and development through modulating RNA metabolism and transport pathways.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many studies have demonstrated that miR-7 is a tumor suppressor, and the downregulation of miR-7 is usually closely related to the occurrence and development of tumors [ 19 , 20 , 21 ]. Based on the previous research progress, our team found that the -604 and -617 sites of the miR-7-2 promoter region in lung cancer tissues were mutated, and miR-7 expression with promoter site mutation was lower than that with non-mutated in tumor tissues.…”
Section: Microrna Genomic Variationmentioning
confidence: 99%